The relationship between dependence on social networking sites and levels of Iraqi youth’s knowledge of the drug phenomenon (Field study applied to drug phenomenon) - SAFAA ALI JABBAR , DR. (lark, 2024)
The research aims to determine the compatibility between reliance on social networking sites and the levels of knowledge of Iraqi youth about their phenomenon. This research is a descriptive study as it is appropriate to determine the role that social networking sites play in increasing the level of knowledge about the conference phenomenon and providing Iraqi youth with information about the phenomenon. The naked eye survey method of the Iraqi public, which represents the female, urban, scientific and rural community, with their clarifications and age. The study indicates the importance that appeared in the development at the appropriate time because it took a special place in Iraqi society, which was previously safe from its advocates, and now it has begun to penetrate the mediation of youth, and the importance of the social networking site Facebook has expanded on information about this phenomenon by Iraqi youth. The results of the study showed that these sites contributed to increasing awareness of the phenomenon, and that the users appeared to be young people. The influence of the study was that they had the ability to educate themselves about the phenomenon of drugs. These sites became an important part of the study’s interests in creative youth research, and these research sites helped in reducing the risk of drug abuse. The emergence of that phenomenon and recognition and knowledge of information about the phenomenon of the phenomenon.